Silicon-on-insulator waveguide as an optical taper in a fiber-to-the-home (FTTH) network - Nurdiani, Zamhari; Nordiana, Rajaee (2024)
An optical signal taper is a passive optical device used to taking a small amount of the signal from the main signal in fiber-to-the-home (FTTH) passive optical network (PON) transmission line. It can be designed using silicon-on-insulator (SOI) material with large cross-section rib waveguide (LCRW). The purpose of this research is to identify and analyse the performance of four different geometries of parallel waveguides to design the optical signal taper. The optimum design can be achieved by selecting the correct geometric criteria such as the shortest parallel waveguide, the largest normalized output power value and the lowest loss among the four geometries. The FTTH wavelength of 1550 nm for the video signal and 1480 nm for the data signal were used as the input signals while the simulations were performed using OptiBPM software. Among the four geometries, the asymmetrical without outer slab geometry gives the smallest waveguide length as well as the highest output power. However, it generated the highest loss up to 2.15%. Therefore, the symmetrical waveguide geometry is chosen to design an optical signal taper where it provides optimum performance. The normalized output power is 2.40% of the 1480 nm signal and 1.90% of the 1550 nm signal while the loss is less than 0.5%.